ANALISIS KUALITAS LAYANAN ADMINISTRASI AKADEMIK TERHADAP KEPUASAN MAHASISWA PADA FAKULTAS DAKWAH DAN KOMUNIKASI UIN ALAUDDIN MAKASSAR - Kamaluddin Tajibu (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2019)
Higher Education Institution (PT) is an educational unit that organizes higher education, whose function is known as the Higher Education Tridarma, namely Education, Research and Community Service. In relation to these functions, academic services at each Faculty become a barometer of the success of the University in fulfilling its functions and roles.